KANDUNGAN BAHAN ORGANIK DAN BEBERAPA SIFAT FISIK TANAH SAWAH PADA POLA TANAM PADI-PADI DAN PADI SEMANGKA - Erwita Pardosi Erwita Pardosi; Jamilah Jamilah2; Kemala Sari Lubis (Universitas Sumatera Utara, 2013)
Most of farmers using crop rotation of rice- watermelon to residuemanure straws fromharvested rice at Air Hitam Village, Lima Puluh Distric. The research was conducted to study somephysical characteristics and soil organic matter at two crop rotation (rice – rice and rice -watermelon). The samples were taken at 0 – 20 cm soil depth and at there plots each crop rotation.The parameters of soil measured were temperature, total porosity, bulk density, permeability andorganic matter. The result showed that all parameters were not different significantly between croprotation of rice – rice and rice – watermelon except soil temperature.